PSXI-39 Effect of legume inclusion and nitrogen fertilization on ammonia volatilization from cattle excreta in tropical grassland. (7th December 2018) - Longhini, V; Cardoso, A; Berça, A; Boddey, R; van Cleef, F; Reis, R; Ruggieri, A
Abstract: Ammonia (NH3 ) is a large source of environmental contamination from nitrogen usage. The objective of this study was to evaluate NH3 losses from urine and dung of cattle grazed in Marandu-grass pastures ( Brachiaria brizantha cv. Marandu) with different sources of nitrogen. The experiment consisted of two factors (pasture management and excreta type) in a randomized complete block design, with 5 replicates. The pastures were: 1) CONTROL: Marandu-grass pastures without nitrogen or legume; 2) FERT: Marandu-grass pastures fertilized with nitrogen (150 kg N ha -1 year -1 ); 3) MIXED: Marandu-grass pastures intercropped with Pinto peanut ( Arachis pintoi cv. Amarillo). The excreta types were dung (1.6 kg/ treatment) and urine (1.0 L/ treatment) from heifers (353.1 ± 24.1 kg BW) grazing in the pastures. Ammonia volatilization was evaluated using semi-opened free static chamber and nitrogen determination by steam distillation. Sampling were performed on 1, 3, 5, 9, 14 and 21 d after treatments being applied to the area. ANOVA was performed for total ammonia volatilized; when differences were observed among means, they were compared using the LSD test. For dung, NH3 losses differed among pasture treatments ( P = 0.046). Volatilization losses was greater for FERT pastures (1.04% of applied N) compared with CONTROL (0.83% of applied N) and MIXED (0.81% of applied N) pastures. No differences were observed for urine among treatments for FERT (3.69 of applied N), MIXED (3.63 of applied N) and CONTROL (2.78 of applied N). The NH3 emission factor differed between excreta type ( P < 0.0001). Urine averaged 3.40% and dung 0.89% of volatilized N-applied. Urine was the main source of ammonia volatilization, and all estimates of volatilization losses were among the lowest reported in the literature.